Co-occurrence of neurofibromatosis type 1 and pseudoachondroplasia – a first case report - Sára Pálla; Pálma Anker; Klára Farkas; Dóra Plázár; Sándor Kiss; Péter Marschalkó; Zsuzsanna Szalai; Judit Bene; Kinga Hadzsiev; Zoltán Maróti; Tibor Kalmár; Márta Medvecz (BMC Pediatrics, 2023)
Abstract Background Neurofibromatosis type 1 and pseudoachondroplasia are both rare autosomal dominant disorders, caused by pathogenic mutations in NF1 and COMP genes, respectively. Both neurofibromin 1 and cartilage oligomeric matrix protein (COMP) play a role in the development of the skeleton. Carrying both germline mutations has not been previously reported; however, it can affect the developing phenotype. Case presentation The index patient, an 8-year-old female presented with several skeletal and dermatologic anomalies resembling the coexistence of multiple syndromes. Her mother had dermatologic symptoms characteristic for neurofibromatosis type 1, and her father presented with distinct skeletal anomalies. NGS-based analysis revealed a heterozygous pathogenic mutation in genes NF1 and COMP in the index patient. A previously unreported heterozygous variant was detected for the NF1 gene. The sequencing of the COMP gene revealed a previously reported, pathogenic heterozygous variant that is responsible for the development of the pseudoachondroplasia phenotype. Conclusions Here, we present the case of a young female carrying pathogenic NF1 and COMP mutations, diagnosed with two distinct heritable disorders, neurofibromatosis type 1 and pseudoachondroplasia. The coincidence of two monogenic autosomal dominant disorders is rare and can pose a differential diagnostic challenge. To the best of our knowledge, this is the first reported co-occurrence of these syndromes.